Digital Systematization of the Reconstruction and Assessment Methodology of the Architectural Design Process Research Network-Institutional Repository - Mondéjar Navarro, Juan Manuel (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
The Reconstruction and Assessment Methodology of the Architectural Design Process (RAM-ADP) extrapolates that used in the doctoral thesis on the Jesús Maestro de Valencia Parish Group to the study of other architectural projects. The RAM-ADP can evolve by being systematically implemented by an open access hybrid digital entity as a research network and institutional repository (RN-IR), which would allow numerous symbiotic relationships between documentation centres, researchers and universities, whose consequence it would be the constitution of a body of knowledge of the design process, more grounded, supplementary to the existing one, and compatible with any style of architectural critical research.